Análise Longitudinal dos Fatores Associados a Epidemia/Endemia de Homicídios nas Capitais Brasileiras - Silas Nogueira de Melo; Janderson Rocha; Yata Anderson Gonzaga Masullo (Confins)
There is a need to expand the discussion about the dynamics of violence, as well as the importance of research that focuses on its reflection on public health. The present study seeks to broaden the understanding of the spatial and temporal dynamics of homicides in Brazilian capitals, based on the public database of different federal and state institutions, for the construction of longitudinal regression models. Thus, it became possible to analyze social, demographic and economic factors that influence the epidemic / endemic homicide rates in the main Brazilian cities in the period between 2012 to 2016. As a result, the availability factors of psychoactive drugs and percentage of young males were statistically significant and positively associated with homicide rates, while school performance factors and health professionals (only fixed effects model) were negatively associated with homicide rates. The results support public policies in the area of health and the prevention of lethal violence in Brazilian capitals.